DETERMINATION OF AUDIT DELAY ON REAL ESTATE PROPERTY COMPANIES IN INDONESIA DURING THE COVID-19 PADEMIC - Sri Murtini; Bamiro Nurudeen Babatunde; Ika Wulandari; Rochmad Bayu Utomo ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2022)
This study aims to determine the factors that affect audit delay in real estate property companies in Indonesia. This is a quantitative study that relies on secondary data. The research population is real estate property companies listed on the Indonesia Stock Exchange. The research sample was 48 companies which were taken by purposive sampling technique. The independent variables consist of profitability, company size, and company age. The dependent variable, on the other hand, is audit delay. The data analysis technique was carried out using multiple linear regression analysis. The t-test was conducted to determine the effect of the independent variable on the dependent variable. The results showed that profitability and company size had no impact on audit delay while the company's age has an impact on audit delays. Companies need to pay attention to the time span of audit completion because it is useful for evaluating the financial performance and condition of the company.